Dynamic Capabilities, Flexibility and Competitive Performance Practices Based on IT; Comparison of Public Organizations and Agricultural Businesses - Cindy Puspitafuri; Sudirman Zaid (Journal of Global Innovations in Agricultural Sciences)
The study examines the necessity of information technology (IT)-based transformation across various sectors in the context of Industry 4.0 and Society 5.0, highlighting the critical role of human resource management in public organizations and the essential nature of business digitalization. Through a systematic literature review of 37 recent journals, the findings reveal that dynamic capabilities and IT flexibility are more prevalent in agricultural businesses compared to public organizations. The implications suggest that public organizations should enhance IT governance to improve dynamic capacity focused on human resources, promoting flexibility in IT use. For agricultural businesses, prioritizing the development of IT capacity and enhancing the perceptions and behaviors of farmers and extension workers is crucial for fostering competitiveness. This will optimize the agricultural supply chain and support effective digitalization. Public sector improvement implications: a) Improved IT governance, is public organizations should focus on strengthening their IT governance structures to enhance dynamic capacity, particularly related to human resource management; and b) Improved flexibility is ensuring that IT use in these organizations adheres to flexibility principles will be critical to adapting to changing needs. Agriculture business focus implications: a) Improved capacity is agricultural stakeholders should prioritize improving their IT capacity; b) Improved perceptions and behaviors is improving the perceptions and behaviors of farmers and extension workers is critical to developing dynamic IT capabilities and business flexibility; and c) Effective digitalization, this effort is critical to optimizing the agricultural supply chain and ensuring the success of the digital transformation of agricultural practices.